Pengaruh Kualitas Pelayanan dan Religiusitas terhadap Keputusan Menggunakan Produk Tabungan Bank Syariah Indonesia Kantor Cabang Pembantu Ponorogo Soetta - Fegga Fisetya Rahmadi Putera; Yulia Anggraini (Falahiya: Journal of Islamic Banking and Finance, 2024)
Introduction: In Islamic banking, what is meant by purchasing decisions is the decision to save or use savings products from Islamic banking. This research was conducted due to inadequate service at BSI KCP Ponorogo Soetta for its customers. In addition, customer trust in Islamic banks is still lacking. The main purpose of this research is to examine and analyze service quality and religiosity for the decision to use the BSI KCP Ponorogo Soetta savings product. Research Methods: This research is a research with a quantitative approach. the sample used was 100 respondents. The data analysis method in this study used Partial Least Square (PLS) analysis with the help of the SmartPLS 4 program application. Results: Based on the results of data analysis conducted by researchers, it can be concluded that (1) Service quality has a significant effect on the decision to use savings products (2) Religiosity has a significant effect on the decision to use a savings product. Conclusion: The quality of service and religiosity simultaneously have a significant effect on the decision to use a savings product.